Jayhawker - Beatty, Patricia, 1922- (New York : Beech Tree Books, 1995)
In the early years of the Civil War, teenage Kansas farm boy Lije Tulley becomes a Jayhawker, an abolitionist raider freeing slaves from the neighboring state of Missouri, and then goes undercover there as a spy.
"A Beech Tree paperback book."
Wilson's Children
Wilson's Junior High School
School Library Journal starred
6.2
5-8
Keywords: United States -- History -- Civil War, 1861-1865 -- Juvenile fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; Slavery -- Fiction; Underground railroad -- Fiction; Spies -- Fiction; United States -- History -- 1861-1865, Civil War -- Fiction; Slavery -- Fiction; Underground railroad -- Fiction; Spies -- Fiction